Dark Triad Traits and Perceptions of Sexual Harassment - Brewer, Gayle (Journal of interpersonal violence, 2021)
Those high on Dark Triad traits (narcissism, Machiavellianism, primary and secondary psychopathy) are more likely to engage in sexual harassment and less likely to empathize with others. Few studies have, however, considered the impact of Dark Triad traits on perceptions of sexually aggressive behavior performed by others. The present study investigated the relationship between Dark Triad traits and perceptions of sexual harassment. Heterosexual women (N = 142) aged 18 to 50 years (M = 20.86, SD = 5.62) completed the NPI-16 (Narcissistic Personality Inventory), Mach IV, Levenson Self-Report Psychopathy Scale, and Sexual Harassment Attitudes Questionnaire. Standard multiple regressions were conducted to investigate the extent to which Dark Triad traits predicted victim and perpetrator blame and attitudes toward victim responses to sexual harassment. Primary psychopathy was the only significant individual predictor such that women with higher levels of the trait were more likely to blame the victim and less likely to blame the perpetrator. In addition, primary psychopathy was related to higher endorsement of victim compliance, and lower likelihood of supporting confrontation of the perpetrator.